History of Childhood: the “Discovery” of Everyday Life - A. A. Slezin (Научный диалог, 2019)
Books the publication of which the author considers notable achievements of recent years in the study of the history of childhood in the XX century are reviewed. According to the reviewer, the books by T. M. Smirnova and P. P. Scherbinin make it possible to form a fairly detailed representation of both the everyday life of children and the social policy of the state in the first half of the 20th century. The breadth of the source base of monographic studies, leaving erroneous stereotypes are noted.